2014
DOI: 10.1007/s00586-014-3550-1
|View full text |Cite
|
Sign up to set email alerts
|

Sitting imbalance cause and consequence of post-traumatic Charcot spine in paraplegic patients

Abstract: More investigations are required to fully understand all the mechanisms underlying CSD pathogenesis to prevent it. Until then, a systematic long-term clinical and radiological follow-up in all post-trauma paraplegic patients is suggested. Combined anterior and posterior fusion, when feasible, can restore the sagittal balance providing a better quality of life in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
(18 reference statements)
0
8
0
Order By: Relevance
“…5 In paraplegic patients lumbar lordosis is flattened and kyphosis might develop, which may intensify further degenerative changes. 13,14 This explains the predominance of the mentioned spine areas (as also seen in cases 1-4), where the L3/4 segment seems to be affected the most. 4 Other risk factors may include spinal fusion and laminectomy for the treatment of SCI as well as very active paraplegic patients.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…5 In paraplegic patients lumbar lordosis is flattened and kyphosis might develop, which may intensify further degenerative changes. 13,14 This explains the predominance of the mentioned spine areas (as also seen in cases 1-4), where the L3/4 segment seems to be affected the most. 4 Other risk factors may include spinal fusion and laminectomy for the treatment of SCI as well as very active paraplegic patients.…”
Section: Discussionmentioning
confidence: 67%
“…Sitting imbalance, an audible cracking noise upon transfer, pain in an otherwise insensitive area and a change in the neurological status seem to be the most frequent ones. 3,4,8,13 Noteworthy changes in the spasticity, usually toward a flaccid paralysis might occur at the time of CSA diagnosis. 3 Interestingly patient 2 presented with increased spasticity, but this might have also been present due to a urinary tract infection at that time.…”
Section: Discussionmentioning
confidence: 99%
“…There is some controversy in the literature concerning spinopelvic alterations in SCI patients with upper thoracic injury level [21,22], while there is a paucity of literature that directly addresses sagittal imbalance in paraplegic patients. Some studies have shown significant alterations of the sagittal thoracolumbopelvic but not of the cervical alignment parameters in the nonambulatory paraplegic patients compared to ambulatory patients, depending on the level of the SCI [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, with advances in medical care, traumatic spinal cord injuries are the leading cause of CSA [2,5]. Between 1978 and 2018, over 140 post-traumatic CSA cases have been reported in the literature [2,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%